2022
DOI: 10.1177/09544054221092910
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on mechanical behavior of clinched joints produced with dissimilar dies

Abstract: The advantages of well-distributed material flow, easy demolding, and good mechanical interlock structure of the extensible die provide the possibility to be widely used in joining lightweight components. In order to explore the differences in the mechanical properties of the joints produced by different dies, the mechanical behavior of the clinched joints made by the fixed die and extensible dies of 2, 3, and 4 movable segments was investigated in the present study. The process of forming evolution, geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…21 To increase strength and improve the material flow of the clinched joints, much research has focused on the proper selection and optimization of forming tools and process parameters. 22,23 Lambiase 24 used experimental and numerical analysis to investigate forming tool design in clinching processes with extensible dies. The results showed that using a larger diameter punch and die or reducing the depth of the die increased the value of the neck thickness.…”
Section: Introductionmentioning
confidence: 99%
“…21 To increase strength and improve the material flow of the clinched joints, much research has focused on the proper selection and optimization of forming tools and process parameters. 22,23 Lambiase 24 used experimental and numerical analysis to investigate forming tool design in clinching processes with extensible dies. The results showed that using a larger diameter punch and die or reducing the depth of the die increased the value of the neck thickness.…”
Section: Introductionmentioning
confidence: 99%